Evaluation of research strategies applied to Workplace Health Promotion - Gonçalo, Camila Silva; Mialhe, Fabio Luiz (Brazilian Dental Science, 2012)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Introduction: Workplace Health Promotion (WHP) is conceptualized as a set of strategies and interventions to help people change their lifestyles and the environment where they develop their activities seeking to reach an optimum state of health. Objective: To present the results of a critical literature review about the more used research strategies and themes studied relation to health promotion at workplace. Methods: We conducted a bibliographical research on the American Journal of Health Promotion. This journal was chosen because it contained important studies about WHP. We only included observational and interventional studies published from 2005 to 2009. Results: Thirty-two articles were included in this research. The observational studies were the most cited design than interventions studies. The measurement procedures most used were questionnaire (n= 14; 44%) and telephone survey (n=6; 19%). The two themes more recurrent in the analyzed articles were: financial questions (n=9;28%) and smoking control (n=5;15,5%). The dental health (n=1;3%) and the stress management (n=1;3%) were the two themes less present among the articles analyzed. Final considerations: The WHP was exploited in various ways and the studies analyzed presented different types of evaluation. These data can support the planning and the actions with intersectoral and multidisciplinary approach when implementing strategies to WHP. Keyword: Health Promotion - Workplace - Occupational Health <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->